Effect of pH on adsorption and desorption equilibria and kinetics of 2-nitrophenol and phenol onto two activated carbons. - Karimi-Jashni, Ayoub. (University of Ottawa (Canada), 1994)
The objective of this thesis was to investigate the impact of pH on the adsorption equilibria, adsorption kinetics, desorption equilibria and desorption kinetics. A study was conducted by using 2-nitrophenol (2NP) and phenol as organic pollutants and F-400 and WV-B carbons as adsorbents. The batch adsorption isotherms study showed that at pHs less than pK$\rm\sb{a}$ (undissociated form of compounds), 2NP and phenol adsorption was markedly higher than at pHs greater than pK$\rm\sb{a}$ (dissociated form of compounds). Both carbons were similarly impacted by pH in the adsorption process and they had almost the same adsorption capacity in adsorbing phenol while F-400 showed more adsorption capacity in adsorbing 2NP. Adsorption-desorption experiments showed that the adsorption of 2NP by F-400 carbon is fully reversible. The presence of 1% NaCl solution did not affect the extent of reversibility. Accordingly, experiments showed both carbons were similarly impacted by pH in the desorption process. For both compounds, the extent of desorption was much greater for the pHs greater than the pK$\rm\sb{a},$ i.e. when the adsorbate is in its dissociated form. Much greater desorption at high pHs suggests that in an electrochemical regeneration process there is a higher probability of regeneration through enhanced desorption at the cathode, because it has a high localized pH. The initial adsorption and desorption rates were significantly affected by pH. Adsorprion kinetics of 2NP onto both carbons were described by the homogeneous surface diffusion model and it was not necessary to utilize separate terms for slow and rapid adsorption mechanisms. Also, it was found that the surface diffusion coefficient, D$\rm\sb{s},$ within the HSSD model was essentially the same at all pHs. (Abstract shortened by UMI.)
Keywords: Engineering, Civil.